GLOBAL WARMING, THE ENVIRONMENTAL CRISIS AND SOCIAL JUSTICE IN YEMEN. Issue 4 (7th August 2020) - Lackner, Helen
Abstract: This article summarises the major environmental and social justice issues facing Yemen, with a discussion of climate change, the impact of the war, oil extraction practices and water use. It also includes two brief case studies as examples of the impact of these issues in worsening inequality: first, the series of disastrous floods in 2020 and, second, the situation in Soqotra.